Magnetic resonance imaging measurement of the femoral antetorsional angle: Comparison with computer tomography and clinical application in a diagnostic algorithm - Ewa Tramś; Maciej Liszka; Krzysztof Kuliński; Kamila Malesa; Marcin Tyrakowski; Jerzy Białecki; Rafał Kamiński (Journal of Experimental Orthopaedics)
Abstract Purpose The purpose of this study was to compare five different femoral torsion measurement methods using computed tomography (CT) and magnetic resonance imaging (MRI), and to develop an MRI‐based rotational profiling technique that is comparable to and as repeatable as CT. Study Design: Diagnostic Study Methods This prospective study evaluates patients who underwent lower limb rotational profile assessment by MRI and CT between June 2022 and October 2023. Five different measurement methods (Reikerås, Lee, Tomczak, Murphy and Jarrett) were compared to determine the best agreement. The Reikerås method was selected and further evaluated for intraobserver and interobserver reliability, as well as the learning curve, using intraclass correlation coefficients (ICCs). Reliability was assessed using ICCs, while agreement was evaluated through Bland–Altman analysis. Additionally, receiver operating characteristic (ROC) curve analysis with the area under the curve (AUC) was performed. Results ICCs for the agreement between MRI and CT measurements indicated strong reliability (0.904 ± 0.022). The ICCs for intraobserver and interobserver reliability were 0.887 ± 0.026 and 0.871 ± 0.0471, respectively. Bland–Altman plots revealed a mean difference of −0.98° with limits of agreement ranging from −7.89° to 5.93°. The optimal cut‐off point for CT referral was calculated based on ROC curve analysis of MR‐based femoral torsion assessment, identified using the Youden index, at 19.67°, with an AUC of 0.998 ± 0.003, indicating excellent diagnostic accuracy. The learning curve showed an optimal ICC > 0.966 after 63 readings. Conclusion The Reikerås MRI measurement method could replace CT, especially in the paediatric population, as it has shown high agreement, comparable reliability and reproducibility. The cut‐off point for this method is 19.67°. Level of Evidence Level II.